Business Consulting Gómez Ingenieros Contratistas S.A.C. - Jove Carcausto, Raiza Paola (2025)
Gómez Ingenieros Contratistas SAC is a company based in Puno dedicated to the maintenance and execution of roadways, with over 10 years in the market, primarily operating in the southern departments of the country such as Arequipa, Tacna, Moquegua, and Puno. The goal of the consultancy focuses on evaluating and optimizing the current state of the company through optimal collection of information from shareholders and its financial situation, addressing everything from situational analysis to proposed solutions. The main objective is to identify and resolve the company's most critical problems. To this end, a detailed analysis of the company’s external and internal components, as well as a diagnosis of the priority issues, has been conducted. The intention is to offer a viable solution and present an implementation plan that will enable the company to achieve its goals. The method used includes business analysis techniques. The study will cover seven chapters. The first chapter develops the SWOT analysis and also an analysis of the five competitive forces. Chapter two prioritizes the company’s problems. Chapter three employs Pareto and Ishikawa methods to identify the root causes of the main problem. Chapter four ranks possible solutions, determining the implementation of an ERP system. Chapter five develops an implementation plan based on the Balanced Scorecard. Chapter six projects the expected outcomes through analysis of NPV, IRR, and WACC. Finally, conclusions and recommendations are presented. The results of the consultancy indicate that the proposed solution is both feasible and beneficial for the company. The financial projection suggests that the company will be able to improve its performance and competitiveness following the implementation of the plan, which will help overcome current challenges and thrive in the future.